Retorika Komunikasi Politik PKS Lovers Di Sosial Media Dalam Perspektif Dramatistik Kenneth Burke - Dini Safitri (Program Studi Ilmu Komunikasi, 2015)
The purpose of this study provides an overview of political rhetoric PKS Lovers communication in social media post LHI arrested as was charged with corruption in a bribery case kuoata meat imports, with PT Indoguna. Reputation PKS was known as the party of 'clean' anti-corruption be gone. In Social Media, PKS was subjected to insults the haters. But the invective then got a reply from the lovers. The presence of the PKS Lovers enlivens the world of social media. Various texts of political communication, production by PKS Lovers, including support of the lovers, but also became a target of the haters. The research method used a qualitative case study methodology. The results showed the rhetoric of political communication PKS Lovers showed PKS activity is sporadic activity, can't be managed well, and reactive. If there is an attack, they attack, but gave the impression of fanaticism, making target for haters.